Implementasi Sistem Data Logger pada Alat Pemantau Energi Listrik Motor Induksi 3-Fasa Berbasis Arduino Mega 2560 di PT Madu Baru Yogyakarta - Beny Firman; Hariyo Santoso; Sigit Priyambodo; Hadi Prasetyo Suseno; Prastyono Eko Pambudi; RR Yuliana Rachmawati Kusumaningsih (Institut Teknologi Dirgantara Adisutjipto, 2022)
An Induction motor is an electric machine that converts electrical energy into kinetics energy and widely used in the industrial fields. Many disturbances that occur in the motor that cause production to be not optimal as for the problems that occur at PT. Madu Baru Yogyakarta is when there is a disturbance in the three-phase induction motor, workers still use manual methods to analyze the disturbance, so that the time used in the analysis takes a long time even the three-phase induction motor cannot work again. In overcoming this, it is necessary to implement a data logger system that can detect the electrical parameters of a three-phase induction motor in real time, in order to make it easier to analyze existing disturbances through graphs. The voltage sensor CYVS13-34U0 and current sensor SCT-019 will detect the electrical parameters which will then be processed by the Arduino Mega 2560 pro so that the processed data will be stored on the microsd card. The data resulting from the processing are electrical parameters in the form of voltage, current, apparent power, real power, reactive power, and power factor. The data will be saved as a file with .txt format which has an interval of about 1 minute for each storage.